Sejarah Perkabaran Injil di Minahasa, 1831-1942 - F.S. Watuseke (Antropologi Indonesia, 1995)
The spread of Christianity in Minahasa began in 16th Century by Spanish missions. In the middle of the 17th Century the activities of the Catholic Church stopped due to political changes at the arrival of the Dutch. Dutch VOC preachers spread Protestatism which had been taken over in1831 by Nederlandse Zendings Genootschap (NZG). They trained young people to become assistants who used Malay and later on the local language. When the area of activities become more extensive, NZG felt that the financial burden was too high so that in 1975 the activities were taken over by the Indische Kerk. At that time the largest church in Minahasa was built, and schools for women and secondary school (MULO) were established The GMIM (gereja masehi Injil Minahasa) was founded in 1934. Although it had autonomy it was still related with the Indische Kerk and headed by Dutch clergymen. When the Japanese invaded, the head of GMIM Synod wa repalced by a Minahasan.